2017
DOI: 10.5539/jel.v6n2p326
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Educational Neuromyths among Teachers and Teacher Candidates

Abstract: The aim of study is to determine the neuromyth level of teachers and pre-teachers and reveal if there is significant difference in terms of some variables (gender, class, etc.). Research was designed in survey model. The research sample was formed with 241 teachers and 511 teacher candidates. In the collection of data, "Educational neuromyhts test" that has 31 questions with options "right, wrong, I have no idea" that was created by the authors by applying reliability studies. Score that can be taken from meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The results presented in this study confirm previous findings that it is not just in-service teachers who believe in neuromyths – a large share of pre-service teachers endorse them as well (Howard-Jones et al, 2009; Fuentes and Risso, 2015; Dündar and Gündüz, 2016; Canbulat and Kiriktas, 2017; Düvel et al, 2017; Kim and Sankey, 2017; Papadatou-Pastou et al, 2017; Im et al, 2018). Out of a total of 11 misconceptions (neuromyths) about learning and memory, the existence of learning styles (93%), the effectiveness of Brain Gym (92%), and the assumption that information is stored in specific locations (hard drive) (85%) were endorsed most frequently.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented in this study confirm previous findings that it is not just in-service teachers who believe in neuromyths – a large share of pre-service teachers endorse them as well (Howard-Jones et al, 2009; Fuentes and Risso, 2015; Dündar and Gündüz, 2016; Canbulat and Kiriktas, 2017; Düvel et al, 2017; Kim and Sankey, 2017; Papadatou-Pastou et al, 2017; Im et al, 2018). Out of a total of 11 misconceptions (neuromyths) about learning and memory, the existence of learning styles (93%), the effectiveness of Brain Gym (92%), and the assumption that information is stored in specific locations (hard drive) (85%) were endorsed most frequently.…”
Section: Discussionsupporting
confidence: 90%
“…One study of post-graduate teacher trainees found that 56–83% of respondents encountered educational programs based on neuromyths in their first year working in schools, which was associated with high levels of acceptance of those myths (Howard-Jones et al, 2009). Studies by Fuentes and Risso (2015, Spain), Dündar and Gündüz (2016, Turkey), Canbulat and Kiriktas (2017, Turkey), Düvel et al (2017, Germany), Kim and Sankey (2017, Australia), Papadatou-Pastou et al (2017, Greece), and Im et al (2018, South Korea) indicate that neuromyths are already present during the academic stage of teacher education. However, no studies focusing on neuromyths related to learning and memory have been conducted with pre-service samples either.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a lack of large effects, the literature evaluated has shown that the higher the score in general knowledge about the brain, the fewer are the neuromyths correctly identified (Dekker et al, 2012 ; Gleichgerrcht et al, 2015 ; Ferrero et al, 2016 ; Canbulat and Kiriktas, 2017 ; Kim and Sankey, 2017 ; Papadatou-Pastou et al, 2017 ; Varas-Genestier and Ferreira, 2017 ; van Dijk and Lane, 2018 ; Tovazzi et al, 2020 ). Nevertheless, studies have also revealed opposing data (Dekker et al, 2012 ; van Dijk and Lane, 2018 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two survey studies were therefore included. Another study (Canbulat and Kiriktas, 2017) was not clear and no additional information was available. Two emails were sent to the corresponding author with a request for clarity, but no response was received.…”
Section: Study Selectionmentioning
confidence: 99%